WEB-BASED FACIAL SKIN TYPE CLASSIFICATION SYSTEM BASED ON BAUMANN'S THEORY - Budi Tjahjono; Dian Fajar Septianto; Gerry Firmansyah; Yulhendri; Suhatati Tjandra (LPPM Nusa Mandiri, 2026)
The skin is a crucial organ in the human body, serving not only as the primary protective barrier but also exhibiting diverse characteristics such as specific types and conditions. Increasingly, people are recognizing the importance of skin care in their daily routines. However, a lack of understanding about different skin types and appropriate skin care products can pose challenges. This research aims to develop a facial skin type classification system based on the existing system. The development of this facial skin type classification system refers to Baumann's Theory, which categorizes skin into four characteristics: Hydration, Sensitivity, Pigmentation, and Aging. The system was developed using the Waterfall methodology and tested using Black Box Testing. The results of Black Box Testing demonstrate that the system functions well and meets the specified requirements. All features and functionalities operate optimally without significant bugs, indicating the success of the Waterfall approach in producing a reliable and ready-to-use system. This system is expected to assist users in accurately identifying their skin type and receiving appropriate skincare solutions, thereby improving the health and appearance of their facial skin.